Design and simulation of a theoretical model for floating microrobots for wastewater treatment (2021)
The document introduces two types of soft microrobots, a planar microrobot with nickel and magnet plates symmetrically distributed onto a polymer with the aim to be able to float in stability, while the other is a starfish-shaped microrobot that imitates the locomotion of echinoderms with a planar center modeled as a rigid body with five fins attached with an axial separation of 30° each. The first one aims to float while the second aims to swim by the movement of the fins. The theoretical models for each microrobot are presented, simulated, and partially proved experimentally. At last, the results showed that the planar microrobot with the initial dimensions does not float, but its floating capacity can be controlled by the dimensions of its geometry, finally proposing a new microrobot with different dimensions. On the other hand, the starfish microrobot results in the centimeter scale showed that the displacement, pressure, and velocity at t=1 s are 1.5 cm, 284 x10^(-4) Pa, and 20 mm/s, respectively, which indicates that the locomotion is actually very fast compared to other methods. These results could be extrapolated to work on the microscale.